Exploiting Labels in Structural Operational Semantics - Mosses, Peter D. (BRICS Report Series, 2005)
Structural Operational Semantics (SOS) allows transitions to be labelled. This is fully exploited in SOS descriptions of concurrent systems, but usually not at all in conventional descriptions of sequential programming languages. This paper shows how the use of labels can provide significantly simpler and more modular descriptions of programming languages. However, the full power of labels is obtained only when the set of labels is made into a category, as in the recently-proposed MSOS variant of SOS.